Development of over voltage and under voltage protection system using trip switch - Nor Fadzilah binti Ismail (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Trip switch is system that applies to protect electrical and electronic equipment from damage when the over voltage and under voltage. This system is being used in daily work for domestic such as house. Traditionally, the electrical and electronic equipment do not have protection if over voltage and under voltage is occurring. Thus, the users need to buy new equipment if over voltage and under voltage is occur. At the same time, the LED will be light up and the buzzer will be sound when the over voltage and under voltage is occur. This system does not interfere other system in house. The system is available for user that single phase equipment. When the main voltage is higher and less than limited voltage set, relay to cut off the main supply from load.